The Influence of the Independent Board of Commissioners and Corporate Sustainability on Firm Value in Mining on the Indonesia Stock Exchange (IDX) in 2021-2022 - Nur'Illiyyien; Fratiwi, Sri Ayu; Tikupasang, Medyoto; Fitriani; Jamaluddin; Habbe, Abdul Hamid; Mediaty (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
Abstract This research aims to examine the effect of the independent board of commissioners and corporate sustainability on firm value. This research uses a causality quantitative approach. The research data is secondary data taken from the IDX data website. The sample used amounted to 15 mining sector companies during the two-year observation period. Purposive sampling is a technique used for data collection. The analysis method used is linear regression analysis with SPSS 23 analysis tool. The results showed that the independent committee and corporate sustainability have a significant influence on firm value. Keywords: Independent Board of Commissioners, Corporate Sustainability, Firm Value